The Majority of 30-Day Readmissions after Intracerebral Hemorrhage are Related to Infections - Lord, Aaron S. (Stroke, 2016)
BACKGROUND AND PURPOSE: Infections are common after intracerebral hemorrhage (ICH), but little is known about risk of serious infection requiring readmission after hospital discharge. METHODS: In order to determine if infections are prevalent in patients readmitted within 30-days of discharge, we performed a retrospective cohort study of patients discharged from non-federal acute care hospitals in California with a primary diagnosis of ICH between 2006 and 2010. We excluded patients who died during the index admission, were discharged against medical advice, or were not California residents. Our main outcome was 30-day unplanned readmission with primary infection-related ICD-9CM code. RESULTS: There were 24,540 index ICH visits from 2006 to 2010. Unplanned readmissions occurred in 14.5% (n=3,550) of index patients. Of 3,550 readmissions, 777 (22%) had an infection-related primary diagnosis code. When evaluating primary and all secondary diagnosis codes, infection was associated with 1,826 (51%) of readmissions. Other common diagnoses associated with readmission included stroke-related codes (n=840, 23.7%) and aspiration pneumonitis (n=154, 4.3%). The most common infection-related primary diagnosis codes were septicemia (n=420, 11.8%), pneumonia (n=124, 3.5%), urinary tract infection (n=141, 4.0%), and gastrointestinal infection (n=42, 1.2%). Patients with a primary infection-related ICD-9CM code on readmission had higher in-hospital mortality compared to other types of readmission (15.6% vs. 8.0%, p<0.001). After controlling for other predictors of mortality, primary infection-related readmissions remained associated with in-hospital mortality (RR=1.7, 95% CI 1.3–2.2). CONCLUSIONS: Infections are associated with a majority of 30-day readmissions after ICH and increased mortality. Efforts should be made to reduce infection-related complications after hospital discharge.